2020
DOI: 10.1093/qjmed/hcaa052.016
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pregnancy related AKI in Egyptian patients: Incidence, Risk factors and Outcome

Abstract: Background Acute kidney injury (AKI) is a serious problem during pregnancy. Once occurred, it causes devastating maternal and fetal outcomes. In developed nations, the trend of pregnancy-related AKI (PRAKI) is on a decline due to the advances in obstetrics care and the legality of abortion. On the contrary, this situation remains a major health problem in the developing countries. Aim of the work in the present study, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 14 , 15 , 16 One of the largest centers from Pakistan reported that 25.6% (n=1441) of patients who presented with AKI were experiencing pregnancy-related AKI in the period from 1990 to 2014. 17 Other countries like Egypt, 6 , 18 , 19 Nigeria 20 , 21 , 22 and DRC 23 have a few single center reports on the incidence and outcomes of pregnancy-related AKI; however, these do not provide the national burden of pregnancy-related AKI in each country.…”
Section: Burden Of Pregnancy-related Aki In Low-income and Lower-midd...mentioning
confidence: 99%
See 2 more Smart Citations
“… 14 , 15 , 16 One of the largest centers from Pakistan reported that 25.6% (n=1441) of patients who presented with AKI were experiencing pregnancy-related AKI in the period from 1990 to 2014. 17 Other countries like Egypt, 6 , 18 , 19 Nigeria 20 , 21 , 22 and DRC 23 have a few single center reports on the incidence and outcomes of pregnancy-related AKI; however, these do not provide the national burden of pregnancy-related AKI in each country.…”
Section: Burden Of Pregnancy-related Aki In Low-income and Lower-midd...mentioning
confidence: 99%
“…Moreover, maternal and fetal mortality rates were very high. 6 , 18 , 19 In Pakistan, 1 study showed that the risk factors for pregnancy-related AKI included perinatal bleeding, placental abruption, intrauterine fetal death, sepsis, pre-eclampsia, and eclampsia. Other rare causes included surgical trauma, exposure to nephrotoxic antibiotics, and hemolysis with blood transfusion reaction.…”
Section: Risk Factors Of Pregnancy-related Akimentioning
confidence: 99%
See 1 more Smart Citation